Q-switched Erbium Doped Fiber Laser Incorporating Antimony (III) Telluride in Polyvinyl Alcohol as Saturable Absorber - Ismail, Ezzatul Irradah; Ashraf Zolkopli, S Muhammad; Lokman, Muhammad Quisar; Yahaya, Hafizal; Harun, Sulaiman Wadi; Ahmad, Fauzan (Institute of Advanced Engineering and Science, 2018)
In this paper, we demonstrated a Q-switched erbium doped fiber laser (EDFL) incorporating Antimony (III) Telluride (Sb 2 Te 3 ) in polyvinyl alchohol (PVA) as passive saturable absorber. The saturable absorber was fabricated by dissolving Antimony (III) Telluride powder into PVA solution and dry in the ambient temperature for 48 hours. Then, 1 mm 2 x 1 mm 2 Sb 2 Te 3 -PVA film based saturable absorber were sandwiched in between FC/PC ferrule for Q-switched laser generation. The stable and self-started Q-switched laser operates at center wavelength 1560 nm with 3 dB bandwidth of 0.23 nm. The laser operates at pump power of 29.3 mW until 84.9 mW with repetition rate of 20.99 kHz to 89.29 kHz and pulse width of 13.95 µs to 5.10 µs. At maximum pump power, the laser able to achieve pulse energy of 62.72 nJ and high signal to noise ratio of 71.4.